Surgical treatment of cervical disc protrusion causing intracranial hypotension following chiropractic manipulation. Issue 9 (September 2015) - Wilson, David; Steel, Timothy; Sutton, Ian
Abstract: We describe a woman with intracranial hypotension provoked by a combination of calcified disc protrusion and chiropractic manipulation who required surgical intervention for definitive treatment. Intracranial hypotension is a rare but increasingly well recognized cause of orthostatic headache that arises due to spinal cerebrospinal fluid leakage from meningeal diverticula or dural perforations.